The Cost Implications of Replacing Soda Lime with Amsorb Plus in Clinical Practice. (23rd November 2011) - Ahmed, Osman; Mannion, Stephen
Abstract : Background and Goal of the Study . Desiccated soda lime is known to produce toxic compounds when interacting with volatile anesthetic agents. Amsorb Plus does not produce these but is more expensive per unit weight. Materials and Methods . In a prospective cross-over study, we evaluated the cost of using soda lime (Spherasorb, Intersurgical, UK) and Amsorb Plus. In four operating theatres over two 4-week periods, one for each product, we measured sevoflurane consumption, amount of absorbent used (kg), and amount of waste disposal (kg). Soda lime was changed weekly, and Amsorb Plus once colour change happened. Both were changed if inspired CO2 occurred. Low fresh gas flows were encouraged with Amsorb Plus. Results and Discussion . The total costs over each four-week period were €4375.69 and €3150.94 for soda lime and Amsorb Plus respectively. Reduced cost during Amsorb Plus period (28%) was due to (1) less sevoflurane consumption, (2) fewer Amsorb Plus changes because of reliable colour change, and (3) cheaper domestic waste disposal of Amsorb Plus as it is inert. Conclusion . We demonstrated Amsorb Plus to be a cost-efficient alternative to soda lime in everyday clinical practice.